Control interno y contrataciones del estado en la Municipalidad Provincial de Maynas 2019 - Flores Echevarria, Christian Adolfo (2023)
The present investigation entitled: internal control and state hiring in the provincial municipality of Maynas, 2019, had as a general objective. Determine the relationship between internal control and state hiring in the Provincial Municipality of Maynas, 2019. The type of research is descriptive, with a cross-sectional, non-experimental design, and was carried out with a sample of 382 residents. It is concluded that Internal control is related to the contracting and acquisition procedures in the local government of Maynas, as evidenced by the high correlation between both variables, as evidenced by Spearman's Rho value and its unilateral importance. The mismanagement is related to the poor development of existing contracting and acquisition procedures in the municipality.